FAKTOR- FAKTOR KESULITAN MAHASISWA DALAM MENYELESAIKAN TUGAS AKHIR PENELITIAN PADA PRODI PENDIDIKAN EKONOMI FKIP UNTAN - Bambang Genjik Sumartono (Universitas Tanjungpura, 2022)
AbstractThesis final project is a research assignment that must be completed by students in the undergraduate program (S1) at each college. However, many students experience difficulties in completing thesis, this is indicated by the length of the guidance period they have taken. The research aims to describe the types of difficulties / forms of difficulty experienced by students in completing research final assignments (theses) and to see the effectiveness of guidance by supervisors. This type of research is a qualitative descriptive study specifically in the case of class 2013 students in ppapk students of fkip economic education study program. And the subjects of this research are undergraduate students and lecturers of the fkip Untan economic education study program who are carrying out thesis guidance in 2020. The data in this study used a distance interview. Regarding the faktors of student difficulty in completing final research assignments, the question of the difficulty faktor was given to students who were writing a thesis or being guided as well as being informants in this study. The data analysis technique uses the component taxonomy domaen analysis technique and the theme of the results of interviews both in-depth interviews and focused interviews of data verification and source triangulation, namely the head of the economic education study program and the thesis supervisor and students who are preparing a thesis as a requirement for undergraduate examinations in the fkip economic education study program. There are also the results of this research described in the form of conclusions, namely the difficulty faktor of students in completing the final thesis research, both internal and external difficulties, which were obtained from four case informants along with their reviews and findings. These difficulties arise which are motivated by external faktors such as family economic difficulties which have an impact on changes in learning behavior as a result of decreased motivation to study concentration. Keyword : Faktors, Student Difficulty In Completing Research Final Assignment.